2000
DOI: 10.1128/aac.44.4.958-966.2000
|View full text |Cite
|
Sign up to set email alerts
|

Pentamidine Inhibition of Group I Intron Splicing in Candida albicans Correlates with Growth Inhibition

Abstract: We previously demonstrated that pentamidine, which has been clinically used against Pneumocystis carinii, inhibits in vitro a group I intron ribozyme from that organism. Another fungal pathogen, Candida albicans, also harbors a group I intron ribozyme (Ca.LSU) in the essential rRNA genes in almost half of the clinical isolates analyzed. To determine whether pentamidine inhibits Ca.LSU in vitro and in cells, phylogenetically closely related intron-containing (4-1) and intronless (62-1) strains were studied. Spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 48 publications
3
71
0
Order By: Relevance
“…This magnesium requirement is similar to that required for the optimal self-splicing activity of the ribozyme (Miletti and Leibowitz 2000;Zhang and Leibowitz 2001), suggesting that the folding of the native P3-P7 correlates with the natural catalytic activity of the ribozyme. However, this magnesium requirement is much lower than that required for the maximal activity of the first transesterification reaction mimicked by the Ca.L-11 catalyzed substrate cleavage (Xiao et al 2003), indicating that the tertiary interactions stabilized by high magnesium concentrations accelerate the first transesterification reaction, but hinder the self-splicing reaction, which involves two reactions at a single guanosine binding site (Cech 1990).…”
Section: Cooperative Folding Of the P3-p7 Pseudoknot And The Whole Rimentioning
confidence: 69%
“…This magnesium requirement is similar to that required for the optimal self-splicing activity of the ribozyme (Miletti and Leibowitz 2000;Zhang and Leibowitz 2001), suggesting that the folding of the native P3-P7 correlates with the natural catalytic activity of the ribozyme. However, this magnesium requirement is much lower than that required for the maximal activity of the first transesterification reaction mimicked by the Ca.L-11 catalyzed substrate cleavage (Xiao et al 2003), indicating that the tertiary interactions stabilized by high magnesium concentrations accelerate the first transesterification reaction, but hinder the self-splicing reaction, which involves two reactions at a single guanosine binding site (Cech 1990).…”
Section: Cooperative Folding Of the P3-p7 Pseudoknot And The Whole Rimentioning
confidence: 69%
“…The aromatic diamidine pentamidine (PN) displays multiples effects against protozoa, bacteria and fungi (17, 53, 58, 132, 137, 217a, 237). Among the fungi, its effect has been mostly studied against Pneumocystis carinii (95,228), C. neoformans (10), C. albicans (150,162), and A. fumigatus (3). The in vitro effect of PN-plus-ITRA and PN-plus-KETO combinations on 11 C. albicans strains (including one azole-resistant isolate) has also been studied (217a).…”
Section: Combinations Of Antifungal Antibacterial and Anticancer Agmentioning
confidence: 99%
“…It has previously been demonstrated that inhibitors of group I introns that alter the ribozyme folding can act as antimicrobial agents in Candida strains in which the function of such ribozymes is essential for viability (Miletti and Leibowitz 2000;Zhang et al 2002). This report shows that the splicing activity of the C. albicans group I ribozyme is effectively compromised by AONs interrupting the folding of functionally important pseudoknot structures.…”
Section: Implications For Rna-targeted Chemotherapymentioning
confidence: 72%